Implementation of Failure Mode and Effects Analysis in the Maintenance Strategy for the Main Engine Cooling System Pump of Fishing Vessels - Siahaan, Juniawan Preston; Yaqin, Rizqi Ilmal; Tumpu, Mula; Hermawan, Ade; Nugroho, Setyawan Dwi; Prakoso, Bagas; Luthfiani, Febi; Zein, Lukman Adria Saputra (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2025)
The performance of the main engine of a fishing vessel becomes less than optimal when its cooling system does not function properly. Centrifugal pumps, as an important component of the cooling system, require special attention in selecting maintenance methods to maintain stable performance. This study aims to investigate the maintenance strategy of centrifugal pumps in the cooling system of the main engine of a fishing vessel. The Failure Mode and Effects Analysis (FMEA) method is used to analyze maintenance strategies based on RPN values. The resulting RPN value can indicate the maintenance strategy that needs to be carried out. The highest RPN value and the failure mode category that requires special attention are analyzed using a histogram diagram. While the root cause of failure is clarified with a fishbone diagram. The results show that the highest failure mode is damage to the pump impeller due to corrosion. The main cause of this failure is found in the selection of impeller materials that are less suitable for working conditions and the environment. Predictive maintenance strategies are considered as a solution to overcome pump impeller problems. This study provides insight into choosing the right maintenance strategy, especially for fishing vessel engines.